Fenomena Sosial Sumbangan Pembangunan Masjid di jalan raya (Studi Kasus Kecamatan Bintan Timur, Kabupaten Bintan) - pepriyana, Adiya; Mita, Mita; Setiandika Igasi, Teguh (Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
The phenomenon of asking for alms on the road for religious needs is one that is currently happening, but the phenomenon of asking for alms on the main road is certainly not only felt by Muslims, because people of other religions or non-Muslims also feel it because they are also users of the road. . thus causing discomfort for road users. The aim of this research is to find out the phenomenon of donations on this road according to the sociology of religion. The method used is incidental sampling which is a data collection technique by finding respondents by chance in one place without planning. The finding in this research is that each mosque has its own way of seeking funds for the renovation of its mosque, and these actions can be analyzed using Max Weber's theory of social action.